Position statement of the Spanish Association of Paediatrics-Spanish Society of Paediatric Infectious Diseases (AEP-SEIP) on the treatment of Multidrug-resistant bacterial infections - David Aguilera-Alonso; Luis Escosa-García; Walter Alfredo Goycochea-Valdivia; Pere Soler-Palacín; Jesús Saavedra-Lozano; Carlos Rodrigo; Emilia Cercenado; José Tomás Ramos; Fernando Baquero-Artigao (Elsevier, 2019)
A progressive increase in the incidence of infections caused by multidrug-resistant microorganisms is being reported. Among these resistant microorganisms, the main threats are extended-spectrum β-lactamase-, AmpC-, and carbapenemase-producing Gram-negative bacilli, methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus faecium. To address this important problem, it is essential to establish pediatric Antimicrobial Stewardship programs, perform active epidemiological surveillance and develop an adequate infection control policy. The therapeutic approach of these infections is often complex, frequently requiring antibiotics with less experience in children. In this position document made by the Spanish Association of Pediatrics and the Spanish Society of Pediatric Infectious Diseases, the epidemiology and treatment of these infections are reviewed according to the best available evidence. Resumen: En los últimos años se ha evidenciado un incremento en la incidencia de infecciones por bacterias multirresistentes. Las principales amenazas son los bacilos gramnegativos productores de β-lactamasas de espectro extendido (BLEE), AmpC o carbapenemasas, Staphylococcus aureus resistente a meticilina y Enterococcus faecium resistente a vancomicina. Para hacer frente a este problema, es fundamental establecer programas de optimización en el uso de antimicrobianos (PROA) específicos para pediatría, realizar una vigilancia epidemiológica activa y desarrollar una adecuada política de control de infecciones. Su abordaje terapéutico es a menudo complejo y multidisciplinar, precisando frecuentemente el uso de antibióticos con menor experiencia. En este documento de posicionamiento, elaborado por la Asociación Española de Pediatría y la Sociedad Española de Infectología Pediátrica, se revisa la epidemiologia y el tratamiento de estas infecciones siguiendo la mejor evidencia disponible.